The influence of gold mining wastes on the migration-transformation behavior and health risks of arsenic in the surrounding soil of mined-area - Chen, Yu; Liu, Guijian; Zhou, Chuncai; Zhou, Huihui; Wei, Yong; Liu, Yuan (Frontiers in Earth Science, 2023)
Understanding the characteristic heavy metals and their migration-transformation behavior in mining area is essential for the prevention and control of mining pollution. This study selected a gold mine in the Anqing-Guichi ore-cluster region in the Middle-Lower Yangtze metallogenic belt as the research area, the concentrations, and migration-transformation mechanisms of As and typical heavy metals (Cd, Zn, Pb, Cu, Cr, and Ni) in gold mining wastes (mine tailings and sewage sludge) and the surrounding soil (farmland soil and soil in mining area) were investigated. The results showed that the concentration of As was high in both mining wastes and soils, and the geo-accumulation index values of As in soils ranging at 1.44-6.70, indicated that As pollution was severe in the soil. Besides, a close correlation between the concentration of As and the content of iron was observed by XRF analysis, in conjunction with SEM observations, most As-bearing phases are embedded in Fe, O, and Si compounds. According to EDS and XPS results, the Fe-O-As particle was suggested to be Fe-(oxy)hydroxides with absorbed or co-precipitated As. Furthermore, the arsenic phase observed in the soils were consistent with the weathering oxidation products in the tailings, demonstrating that the mineral particles in the tailings could migrate into soils via atmospheric transport, rainwater leaching, surface runoff, etc., and consequently result in heavy metal accumulation. The sequential chemical extraction result showed that the residual state of As in the soil exceeded 60 %, and As posed no risk to low risk according the Risk assessment code result. However, due to the high concentration and high mobility if arsenic, its environmental impact cannot be ignored even if its bio-accessibility in mine soil is low.